2005
DOI: 10.1021/la0469607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Positively Charged Short Peptides on Stability of Cubic Phases of Monoolein/Dioleoylphosphatidic Acid Mixtures

Abstract: To elucidate the stability and phase transition of cubic phases of biomembranes with infinite periodic minimal surface is indispensable from biological and physicochemical aspects. In this report, we investigated the effect of positively charged peptide-3K (LLKKK) and poly(L-lysine) on the phase stability of monoolein (MO) membranes containing negatively charged dioleoylphosphatidic acid (DOPA) (i.e., DOPA/MO membranes) using small-angle X-ray scattering. At first, the effect of peptide-3K on 10% DOPA/90% MO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 36 publications
(81 reference statements)
2
26
0
Order By: Relevance
“…In a basic approach, the molecular shape can be described by the critical packing parameter (CPP) or the molecular wedge shape factor, which is defined as:where v s is the hydrophobic chain volume, a 0 is the headgroup area, and l is the hydrophobic chain length [73]. This packing parameter is controlled by various factors such as surfactant's molecular shape, temperature, hydration, the presence of hydrophilic or hydrophobic guest molecules, and electrostatic effects [16], [29][33], [35], [45][50], [61], [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a basic approach, the molecular shape can be described by the critical packing parameter (CPP) or the molecular wedge shape factor, which is defined as:where v s is the hydrophobic chain volume, a 0 is the headgroup area, and l is the hydrophobic chain length [73]. This packing parameter is controlled by various factors such as surfactant's molecular shape, temperature, hydration, the presence of hydrophilic or hydrophobic guest molecules, and electrostatic effects [16], [29][33], [35], [45][50], [61], [62].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the effect of various peptides on the stability of MO-based cubic phases has been subject of several studies [61][64]. It was found that the electrostatic interactions in the membranes incorporating negatively (or positively) charged lipids are controlling the structural lamellar-nonlamellar transitions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…within the same cell organelle is frequently seen, pointing to the ease with which lamellar and bicontinuous cubic membranes or other organized membrane structures are interconverted. In vitro studies using monoolein membranes containing negatively charged dioleoylphosphatidic acid have shown that the electrostatic interactions caused by surface charge of the membranes [17], charged 2þ short peptides such as poly-L-lysine [18], Ca concentration [19], and low pH [20] play important role in the phase transition between lamellar and cubic phases as well as on the stability of cubic phases. Likewise, the weak molecular interactions, for example, by membrane proteins, may lead to transformation of Endoplasmic reticulum (ER) membrane from lamellar into cubic in mammalian cells suggesting that electrostatic interactions may play an important role in that process [18,21].…”
Section: Cubic Phase Versus Cubic Membranementioning
confidence: 99%
“…In vitro studies using monoolein membranes containing negatively charged dioleoylphosphatidic acid have shown that the electrostatic interactions caused by surface charge of the membranes [17], charged 2þ short peptides such as poly-L-lysine [18], Ca concentration [19], and low pH [20] play important role in the phase transition between lamellar and cubic phases as well as on the stability of cubic phases. Likewise, the weak molecular interactions, for example, by membrane proteins, may lead to transformation of Endoplasmic reticulum (ER) membrane from lamellar into cubic in mammalian cells suggesting that electrostatic interactions may play an important role in that process [18,21]. In a recent experimental study on the effects of divalent cations in the isolation buffers for mitochondria, we were able to demonstrate that the presence of high concentration of Ethylenediaminetetraacetic acid (EDTA) up to 10 mM preserved mitochondrial cubic membranes in vitro (manuscript in preparation).…”
Section: Cubic Phase Versus Cubic Membranementioning
confidence: 99%
“…These have been postulated to play several important biological roles such as membrane fusion, control of functions of membrane proteins, and ultrastructural organization inside cells. One family of cubic phases, which includes the Q 224 phase (space group Pn3m, Schwartz's D surface), Q 229 phase (Im3m, P surface) and Q 230 phase (Ia3d, G surface), has an infinite periodic minimal surface (IPMS) consisting of bicontinu-ous regions of water and hydrocarbon [17][18][19]. We have found that, as the concentration of peptide-1 increased, a phase transition from Q 224 to Q 229 occurred, and that, at higher peptide-1 concentrations, MO/peptide-1 membranes were in the L α phase [16].…”
Section: Analysis Of Shape Changes Induced In Guvs By the Interacmentioning
confidence: 99%